Effects of AntagomiRs on Different Lung Diseases in Human, Cellular, and Animal Models - Murdaca, Giuseppe (Int J Mol Sci, 2019)
Introduction: MiRNAs have been shown to play a crucial role among lung cancer, pulmonary fibrosis, tuberculosis (TBC) infection, and bronchial hypersensitivity, thus including chronic obstructive pulmonary disease (COPD) and asthma. The oncogenic effect of several miRNAs has been recently ruled out. In order to act on miRNAs turnover, antagomiRs have been developed. Materials and methods: The systematic review was conducted under the PRISMA guidelines (registration number is: CRD42019134173). The PubMed database was searched between 1 January 2000 and 30 April 2019 under the following search strategy: (((antagomiR) OR (mirna antagonists) OR (mirna antagonist)) AND ((lung[MeSH Terms]) OR (“lung diseases”[MeSH Terms]))). We included original articles, published in English, whereas exclusion criteria included reviews, meta-analyses, single case reports, and studies published in a language other than English. Results and Conclusions: A total of 68 articles matching the inclusion criteria were retrieved. Overall, the use of antagomiR was seen to be efficient in downregulating the specific miRNA they are conceived for. The usefulness of antagomiRs was demonstrated in humans, animal models, and cell lines. To our best knowledge, this is the first article to encompass evidence regarding miRNAs and their respective antagomiRs in the lung, in order to provide readers a comprehensive review upon major lung disorders.